DAMPAK PANDEMI COVID-19 TERHADAP HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI - Rahmawati, Aulya; Jalaluddin, Jalaluddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study had a purposed to find out the difference of stock price and stock trading volume before and after the pandemic in transportation and logistics sector companies listed on the Indonesia Stock Exchange. The sample taking by purposive sampling method with some criteria and got 22 entities. The data used is secondary sourced from Indonesia Stock Exchange. This study using paired sample t-test for for data that is normally distributed and Wilcoxon Signed-Rank Test for data that is not. The results of this study indicate that There are significant differences in stock prices and trading volumes before and after the first announcement of the Covid-19 pandemic in Indonesia